The Strength of Relationships - Saillant, Said (Stance: an international undergraduate philosophy journal, 2019)
I endeavor to show that Descartes’ attribute-mode distinction cannot be characterized in terms of the determinable-determinate relation. I identify the latter’s formal and modal properties in order to determine whether the former shares them, which ultimately shows distinctness. I then indicate which property accounts for the differences. I conclude that the relation that unites modes under an attribute is weaker than that which groups determinates under some determinable, respectively, the relations of inherence and incompatibility.